NOD2/CARD15 gene polymorphisms and sarcoidosis susceptibility: review and meta-analysis - Chen, Xuping; Zhou, Zhenxing; Zhang, Yi; Cheng, Xiaoliang; Guo, Xiaowen; Yang, Xiaodong (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background: The association between NOD2/CARD15 (nucleotide binding oligomerisation domain containing 2) gene polymorphisms and susceptibility to sarcoidosis have been extensively investigated in recent years. However, the results from previous studies remain controversial. To assess the association of NOD2/CARD15 polymorphisms and sarcoidosis susceptibility, we performed a meta-analysis. Methods: PubMed, Embase, CNKI and Wanfang databases were examined for all relevant studies up until 8th October 2016. In all, 968 cases and 1549 controls in eight case-control studies were included which mainly consisted of Caucasian participants. The relevant data were extracted and the odds ratio (OR) with 95% confidence intervals (95% CI) calculated to assess the strength of any associations. Statistical analyses were calculated using STATA12.0 software and Revman5.3 software. The associations between NOD2/CARD15 SNP rs2066844, rs2066845, rs2066847, rs1861759 polymorphisms and the risk of sarcoidosis were evaluated in allelic, dominant, recessive and additive models. Results: The pooled data showed that the NOD2/CARD15 rs2066845 polymorphism was associated with sarcoidosis susceptibility in allelic model (C vs. G, OR=1.86, 95% CI: 1.14-3.04, P=0.01), dominant model (GC + CC vs. GG, OR=1.84, 95% CI: 1.11-3.05, P=0.02) and additive model (GC vs. GG, OR=1.79, 95% CI: 1.08-2.97, P=0.02). However, the results suggested that the rs2066844, rs2066847 and rs1861759 polymorphisms might not be associated with a risk of sarcoidosis. Conclusions: This meta-analysis indicated that the ‘C’ allele of SNP rs2066845 may be a risk factor for sarcoidosis, especially in Caucasians, whilst rs2066844, rs2066847 and rs1861759 may not be associated with a risk of developing sarcoidosis.